Development of Sulfide Solid Electrolytes and Interface Formation Processes for Bulk-Type All-Solid-State Li and Na Batteries - Hayashi, Akitoshi; Sakuda, Atsushi; Tatsumisago, Masahiro (Frontiers in Energy Research, 2016)
All-solid-state batteries with inorganic solid electrolytes are recognized as an ultimate goal of rechargeable batteries because of their high safety, versatile geometry and good cycle life. Compared to thin-film batteries, increasing the reversible capacity of bulk-type all-solid-state batteries using electrode active material particles is difficult because contact areas at solid–solid interfaces between the electrode and electrolyte particles are limited. Sulfide solid electrolytes have several advantages of high conductivity, wide electrochemical window, and appropriate mechanical properties such as formability, processability, and elastic modulus. Sulfide electrolyte with Li7P3S11 crystal has the highest Li+ ion conductivity of 1.7 × 10-2 S cm-1 at 25 °C. It is far beyond the Li+ ion conductivity of conventional organic liquid electrolytes. The Na+ ion conductivity of 7.4 × 10-4 S cm-1 is achieved for Na3.06P0.94Si0.06S4 with cubic structure. Moreover, formation of favorable solid–solid interfaces between electrode and electrolyte is important for realizing solid-state batteries. Sulfide electrolytes have better formability than oxide electrolytes. Consequently, a dense electrolyte separator and closely attached interfaces with active material particles are achieved via “room-temperature sintering” of sulfides merely by cold pressing without heat treatment. Elastic moduli for sulfide electrolytes are smaller than that of oxide electrolytes, and Na2S-P2S5 glass electrolytes have smaller Young’s modulus than Li2S-P2S5 electrolytes. Cross-sectional SEM observations for a positive electrode layer reveal that sulfide electrolyte coating on active material particles increases interface areas even with a minimum volume of electrolyte, indicating that the energy density of bulk-type solid-state batteries is enhanced. Both surface coating of electrode particles and preparation of nanocomposite are effective for increasing the reversible capacity of the batteries. Our approaches to form solid–solid interfaces are demonstrated.